Intelligent Caching Wireless Data Access in the Wireless Spectrum - Syazwa Mad Jais; Sarina Sulaiman; Siti Mariyam Shamsuddin (Institute of Advanced Engineering and Science, 2013)
The evolution wireless technologies are growing rapidly in upcoming years. It is expected that many users will shift to more advanced devices that will contribute to gain higher demand in wireless spectrum. However, the capacity for the allocation frequency in the wireless spectrum is typically limited in wireless data transmission. Therefore, when the loads of wireless users in the wireless communications are increasing, the need of cache mechanisms such as Web caches or Web servers are crucial. The scalability demands on internet infrastructure keep increasing as the internet continues to grow in popularity and size. Therefore, the existence and development in Web caching technologies will contribute to bandwidth savings, network latency reduction, improve content availability and subsequently server load balancing. This paper will studies and investigates the cache performance in wireless spectrum with the purpose of dealing with the data growth since the spectrum crisis becomes a serious matter lately. The performance improvement will be observed using caching scheme which allows for time shifting and load shifting in accessing the wireless data with the better cache deployment in the network system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2506